One - step selective synthesis of 13-epi-manoyl oxide [Articol] - Morarescu, Olga; Traistari, Marionela; Barba, Alic; Duca, Gheorghe; Ungur, Nicon; Kulciţki, Veaceslav (Institutul de Chimie al AŞM, 2021)
The selective one-step synthesis of 13-epi-manoyl oxide is reported based on a low-temperature superacidic cyclization of sclareol. The reaction conditions have been finely tuned in order to achieve a 9:1 ratio between epimeric oxides in favour of the desired 13-epi-oxide. The structures were confirmed by 1H and 13C NMR, and composition of the crude reaction products determined by GC-MS. These results have been interpreted by a hypothetical SN2 mechanism which occurs with inversion of configuration around the C-13 chiral center of the starting substrate. The preparative value of the elaborated procedure is demonstrated on a gram-scale experiment.
Keywords: sclareol; cyclization; superacid; ether; labdane